Sri Ksetra Museum Collection Inventory - Galloway, Charlotte (Beyond Boundaries, 2022)
The Sri Ksetra Museum Inventory is the most comprehensive single source of Myanmar's Pyu material culture. With artifacts dating from the early centuries of the first millennium, the inventory includes material retrieved from site excavations at Sri Ksetra and surrounding region from the early 1900s to recent years. With many objects documented for the first time, this publication makes the collection accessible to an international audience.